Residual effect of summer legumes incorporation on soil nutrient status and nutrient use efficiency of kharif rice - Sunil Kumar, Tamminaina; Virdia, H. M.; Patel, K. G.; Chowdhury, Manojit; Satya, M. Sri Sai Charan; Mahmoud, Samy F.; Elbeltagi, Ahmed; Salem, Ali; Elwakeel, Abdallah Elshawadfy; El-Shinawy, Doaa M. (Frontiers in Sustainable Food Systems, 2025)
Sustainable nutrient management in rice-based cropping systems is essential to counteract soil degradation and excessive fertilizer dependence. Legume residue incorporation has been proposed as a strategy to improve soil fertility and nutrient use efficiency (NUE), yet its effectiveness under varying fertilizer regimes remains inadequately explored. A field experiment was conducted with four main treatments, i.e., green gram (Vigna radiata), cowpea (Vigna unguiculata), dhaincha (Sesbania aculeata), and fallow combined with six fertilizer regimes in subplots, i.e., 100% RDF (100 kgN + 30 kg P2O5 + 00 K2O kg/ha), 75% RDF (75 kg N + 22.5 kg P2O5 + 00 K2O kg/ha), 50% RDF (50 kg N + 15 kg P2O5 + 00 K2O kg/ha), 75% RDF + 25% N from FYM, 50% RDF + 50% N from FYM, and No-fertilizer application. This study evaluated the effects of legume residue incorporation on soil nutrient status, total nitrogen (N), phosphorus (P) and potassium (K) uptake, and NUE in kharif rice over 2 years and concluded that rice grown in dhaincha-incorporated plots exhibited significantly higher total NPK uptake, improved soil nutrient status, and enhanced NUE, followed by green gram and cowpea. The highest nitrogen and phosphorus recovery was observed in green gram plots under 100% RDF, while fallow plots with no fertilizer application recorded the lowest nutrient uptake and efficiency. Nitrogen use efficiency, agronomic use efficiency was found higher in dhaincha incorporated plots applied with 100% RDF. Preceding summer legumes with residue incorporation could result in nitrogen economy for succeeding kharif, as it responded more in 100% RDF + dhaincha incorporation but at par with dhaincha + 75% RDF + 25% N from FYM. Incorporating dhaincha residues reduced synthetic fertilizer requirements by 20–25%, demonstrating its potential to enhance soil fertility while reducing dependency on chemical inputs.